Guide to Aboriginal assistance - Australia. Department of Aboriginal Affairs (Canberra : Australian Government Publishing Service for the Dept. of Aboriginal Affairs, 1974)
Prepared for an Aboriginal audience; sets out the responsibilities in Aboriginal affairs of Commonwealth and state governments, national and state non-Government organisations, voluntary organisations; lists assistance programs for Aboriginal people.
Index.
Keywords: Welfare services for Aborigines. Australia; Aboriginal Australians -- Services for; Social service -- Australia; Government policy - Self determination - 1972-1984.; Law - Administrative law - Commonwealth; Social welfare; Australia